COGNITIVE-MOTOR INTERACTION AS A RESOURCE FOR EFFECTIVENESS IN ADAPTIVE PHYSICAL EDUCATION - Kozlova Galina Gennadievna (Proximus Journal Publishing, 2025)
This article explores the theoretical foundations of cognitive-motor interaction and its role within the system of adaptive physical education. It substantiates the necessity of an integrated approach that combines motor and cognitive components when organizing physical activities for individuals with health limitations. The paper highlights the importance of neuroplasticity, motivation, movement awareness, and sensorimotor coordination as key factors for enhancing the effectiveness of both corrective and developmental interventions in adaptive physical education.
Keywords: adaptive physical education; cognitive-motor interaction; neuroplasticity